German labor market and fiscal reforms 1999 to 2008: Can they be blamed for intra-Euro Area imbalances? - Niklas Gadatsch; Nikolai Stähler; Benjamin Weigert (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2014)
In this paper,we assess the impact ofmajor German structural reforms from1999 to 2008 on key macroeconomic variables within a two-country monetary union DSGE model. Bymany, these reforms, especially the Hartz reforms on the labormarket, are considered to be the root of thereafter observed imbalances in the Euro Area. We find that, in terms of German GDP, consumption, investment and (un)employment, the reforms were a clear success albeit the impact on the German trade balance and the current account was onlyminor. Most importantly, the rest of the Euro Area benefited frompositive spillover effects. Hence, our analysis suggests that the reforms cannot be held responsible for the currently observed macroeconomic imbalances within the Euro Area.
Keywords: H2; J6; E32; E62; 330; Fiscal Policy; Labor Market Reforms; DSGE modeling; Macroeconomics